2019
DOI: 10.1021/jacs.9b11500
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Monitoring of Crystalline Active Materials and Resistance Evolution in Lithium–Sulfur Batteries

Abstract: Batteries. ChemRxiv. Preprint. Operando X-ray diffraction (XRD) is a valuable tool for studying secondary battery materials as it allows for the direct correlation of electrochemical behavior with structural changes of crystalline active materials. This is especially true for the lithium-sulfur chemistry, in which energy storage capability depends on the complex growth and dissolution kinetics of lithium sulfide (Li2S) and sulfur (S8) during discharge and charge, respectively. In this work, we present a novel … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
76
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 60 publications
(80 citation statements)
references
References 52 publications
4
76
0
Order By: Relevance
“…This linear relationship of = O8/ has been demonstrated in previous work. 9 Above 3.7 V, the k values determined by ICI and GITT with 5-40 s interval are close to each other, which confirms the theoretical derivation in section 2.2 and is corroborated by the EIS results. The GITT results collected from the 50-150 s interval show higher k values and two local maxima between 3.7 and 4.2 V while the k values from other three analyses fluctuate less and are more consistent with each other.…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…This linear relationship of = O8/ has been demonstrated in previous work. 9 Above 3.7 V, the k values determined by ICI and GITT with 5-40 s interval are close to each other, which confirms the theoretical derivation in section 2.2 and is corroborated by the EIS results. The GITT results collected from the 50-150 s interval show higher k values and two local maxima between 3.7 and 4.2 V while the k values from other three analyses fluctuate less and are more consistent with each other.…”
Section: Resultssupporting
confidence: 85%
“…Figure 2 displays the k values, which are √ ⁄normalized by the current (Equation18) from GITT and ICI, and the Warburg coefficients (σ) multiplied by O8/ from EIS fittings. This linear relationship of = O8/ has been demonstrated in previous work 9. Above 3.7 V, the k values determined by ICI and GITT with 5-40 s interval are close to each other, which confirms the theoretical derivation in section 2.2 and is corroborated by the EIS results.…”
supporting
confidence: 89%
“…R corresponds to the sum of electronic, solution and charge transfer resistances, [36] while k characterizes the transport properties in the porous positive electrode. [37] In the resistance plots of the 10 th discharge, it can be observed that R of PO2k-212 is significantly higher than that of the other cells on the lower plateau (Q = 300-1000 mAh gS -1 ) while k is only slightly higher. This substantial difference was reproduced in repeated experiments with this binder, as shown in Fig.…”
Section: Resultsmentioning
confidence: 87%
“…The cells were rested for 6 h before discharged at C/50 (1C = 1672 mA gS −1 ) to 1.9 V and charged at C/25 to 2.6 V. After the formation cycle, the cell was cycled at C/10 between 1.8 and 2.6 V with a 1 s current pause every 5 min for the resistance measurement by the Intermittent Current Interruption (ICI) method. [36,37] Each discharge and charge step was limited to 10 h (time required to discharge/charge a cell with the theoretical capacity) to stop infinite discharging/charging (mostly charging) cause by polysulfide shuttling. The cells were tested on an Arbin BT-2043 battery testing system.…”
Section: Electrochemical Characterizationmentioning
confidence: 99%
“…[10][11][12][13][14] Moreover, the dissolved polysulfides form passivation layers on the cathode and anode surfaces, which give rise to an increase in cell polarization, resulting in the failure of LiÀ S cells. [15][16][17][18][19] Extensive efforts, such as sulfur-confined porous carbons, [20][21][22][23][24][25][26][27] electrolyte additives, [28,29] polysulfide adsorbents, [30][31][32][33] and small sulfur molecules, [22,34] have been devoted to overcoming these challenges. These approaches show promise for LiÀ S batteries, though their electrochemical performances are still not sufficient for practical usage.…”
Section: Introductionmentioning
confidence: 99%